O Tribunal de Contas da União inibe inovações em concessões públicas? - Braga, André de Castro Oliveira Pereira (2015)
For the past 20 years, public concessions promoted by the Brazilian government have been overseen by the Tribunal de Contas da União (TCU), Brazilian supreme audit institution. What are the effects of this oversight? Using data related to contracts audited from 1993 to 2014, we analyse if the TCU prevents innovation in concessions. The empirical results show that there is no significant correlation between innovations and red tape originated in TCU’s audit procedures. On the other hand, we find a significant negative correlation between TCU’s degree of interventionism and the emergence of innovations in public concessions.